The role of ceramide in major depressive disorder - Kornhuber, Johannes; Reichel, Martin; Tripal, Philipp; Groemer, Teja W.; Henkel, Andreas W.; Mühle, Christiane; Gulbins, Erich (European archives of psychiatry and clinical neuroscience, 2009)
Major depression is a severe mood disorder with a lifetime prevalence of more than 10%. The pharmacokinetic hypothesis claims that a slow accumulation of antidepressant drugs by acid trapping mainly into lysosomes is responsible for the therapeutic latency and that a lysosomal target mediates the antidepressant effects. The lysosomal lipid metabolizing enzyme acid sphingomyelinase (ASM) cleaves sphingomyelin into ceramide and phosphorylcholine. In a pilot study, the activity of this enzyme was increased in peripheral blood cells of patients with major depressive disorder (MDD), making the ASM an interesting molecular target of antidepressant drugs. Indeed, several antidepressant drugs functionally inhibit ASM. The ASM/ceramide pathway might be a missing link unifying independent findings in neurobiology and the treatment of MDD such as therapeutic latency, oxidative stress, immune activation and increased risk of cardiovascular disease. © 2009 Springer-Verlag.
Created from Fastlane, Scopus look-up
Keywords: Acid sphingomyelinase; Amitriptyline; Ceramide; Fluoxetine; Lysosomes; Major depressive disorder; Neuroplasticity hypothesis; Pharmacokinetic hypothesis; Sphingolipids